MCME project V.2.0: randomised controlled trial of a revised SMS-based continuing medical education intervention among HIV clinicians in Vietnam. Issue 1 (26th February 2018) - Gill, Christopher J; Le, Ngoc Bao; Halim, Nafisa; Chi, Cao Thi Hue; Nguyen, Viet Ha; Bonawitz, Rachael; Hoang, Pham Vu; Nguyen, Hoang Long; Huong, Phan Thi Thu; Larson Williams, Anna; Le, Ngoc Anh; Sabin, Lora
Abstract : Background: Continuing medical education (CME) is indispensable, but costs are a barrier. We tested the effectiveness of a novel mHealth intervention (mCME V.2.0) promoting CME among Vietnamese HIV clinicians. Methods: We enrolled HIV clinicians from three provinces near Hanoi. The 6-month intervention consisted of (1) daily short message service multiple-choice quiz questions, (2) daily linked readings, (3) links to online CME courses and (4) feedback messages describing the performance of the participant relative to the group. Control participants had equal access to the online CME courses. Our primary endpoint was utilisation of the online CME courses; secondary endpoints were self-study behaviour, performance on a standardised medical exam and job satisfaction. Results: From 121 total HIV clinicians in the three provinces, 106 (87.6%) enrolled, and 48/53 intervention (90%) and 47/53 control (89%) participants completed the endline evaluations. Compared with controls, intervention participants were more likely to use the CME courses (risk ratio (RR) 2.3, 95% CI 1.4 to 3.8, accounting for 83% of course use (P<0.001)). Intervention participants increased self-study behaviours over controls in terms of use of medical textbooks (P<0.01), consulting with colleagues (P<0.01), searching on the internet (P<0.001), using specialist websites (P=0.02), consulting the Vietnam HIV/AIDS treatment guidelines (P=0.02) and searching the scientific literature (P=0.09). Intervention participants outperformed controls on the exam (+23% vs +12% score gains, P=0.05) and had higher job satisfaction. Conclusion: The mCME V.2.0 intervention improved self-study behaviour, medical knowledge and job satisfaction. This approach has potential for expansion in Vietnam and similar settings. Trial registration number: NCT02381743 .